MENJAWAB PEMBENTUKAN AUKUS DI KAWASAN ASIA PASIFIK MENGGUNAKAN PRINSIP BEBAS AKTIF INDONESIA - Azzqy, Andrea Abdul Rahman; Awal, Syahrul (Dinamika Global : Jurnal Ilmu Hubungan Internasional, 2023)
The formation of the AUKUS alliance by the United States, Britain, and Australia in September 2021 concerns Indonesia in maintaining stability and security in the Asia Pacific region. As a key player, Indonesia responded to AUKUS with the principle of "Free and Active" in its foreign policy. This principle allows Indonesia to maintain relations with various powers without firm expressions of support or opposition. Indonesia continues to monitor AUKUS and adopts hedging strategies to reduce risks. This effort involves increasing military capabilities and regional cooperation. Indonesia's stance includes efforts to maintain stability, act as a mediator, and participate in international forums for the sake of peace and cooperation. An approach based on " Free and Active " helps Indonesia maintain positive relations with the United States, Britain, and China, while continuing to play an active role in the stability and security of the Asia Pacific.